THE RESULTS OF THE DEVELOPMENT OF CARING MODEL FOR END OF LIFE PATIENTS IN THE COMMUNITY - Jitbantad, Waranya; Katekumpon, Mingkhuan (Journal of MCU Nakhondhat, 2022)
End-stage patients need continued palliative care, especially in communities where the care model is unclear. Which this research aims to develop and study the effect of the community care model for End of Life patients. The samples were caregivers and patients who were treated at Maharaj Hospital Nakhon Si Thammarat who have been diagnosed by a doctor in the late stage to provide palliative care and relatives or doctors to return to care at home during July 2020 to August 2021, with a score of 50 percent or less according to the Suan Dok Palliative Care Patient Assessment Scale. This study is an action research was divided into 3 phases: 1) Preparing the caregivers at home, consisting of 1) patient assessment methods 2) knowledge about disease and care and 3) training on skills in managing non - symptoms, 4) condition - based care, 5) coordination, and 6) evaluation, 2) Conducting four home visits every 2 weeks, and 3) Evaluation by palliative care outcome scale in patients and care givers. The data were analyzed using descriptive statistics such as percentage, mean and standard deviation. and data analysis before and after with Pair T test statistics. The palliative model was assessed before and after care.The results showed that; A sample of 35 people received care according to the end-stage care model. It was found that the mean of patient care knowledge increased from 7.74 (SD. 2.92) to 15.49 (SD. 0.71). Palliative care outcomes Patients decreased from 23.69 (SD. 4.09) to 5.74 (SD. 1.67), which was a statistically significant improvement (P-Value < 0.000). Patient and relative satisfaction was at the highest level at 46.72. (SD. 1.85) and suffering with reduced symptoms in all symptoms. Therefore, it was concluded that the development of pediatric care models in the community resulted in better palliative care.